Designing of an airport according to ecological noise criteria - Коновалова, О.В. (Proceedings of National Aviation University (archive), 2004)
The analysis of recommendation for assessment of airport development consequences for environment was done. Based on, as an example, Kiev/Zhuliany airport it is shown that the problem of aircraft noise leads to constraints for airport capacity not only for hubs, but also for small airports. Three types of airport capacity and their connection are discussed. On the stage of ecological design it is recommended to use the value of maximum operational capacity to set the zone of protection against aircraft noise and for land-use planning.